The Relationship between Family Independence and Hypertension Treatment in the Elderly - Ilham, Rosmin Ilham; Biahimo, Nur Uyuun I.; Latief, Amalia Fajriani; Paneo, Ibrahim; Rama, Zainuddin (Jambura Nursing Journal, 2024)
Hypertension or high blood pressure is a serious medical condition and will significantly increase the risk of heart, brain, kidney, and other diseases. The aim of the research is to analyze the relationship between family independence and hypertension care in the elderly in Mongolato Village, Telaga District. This research design is descriptive and analytical with a cross-sectional study method carried out in Mongolato Village. With a sample size of 72 with a sample size of 42 people using a purposive sampling technique. Data analysis used the Spearman rho correlation test. The research results obtained mostly 18 respondents (42.9%) with family independence level IV but adequate hypertension treatment, 2 respondents (4.8%), and 8 respondents with family independence II (19.0) but there was 1 respondent (2.4%) with adequate hypertension treatment. The results of the Spearman rho correlation test show that the sig value is p value = 0.000 Î±